The Wasatī and Salafī Approaches to the Religious Law of Muslim Minorities - Shavit, Uriya (Islamic law and society, 2012)
Abstract The article explores the evolution of competing approaches to the religious law of Muslim minorities (fiqh al-aqalliyyāt al-muslima): the wasatī and the salafī. Both approaches are grounded in a similar triumphalist and revivalist contextualization of Muslim presence in the West. The wasatī approach, led by al-Azhar graduates and Islamist activists, presents two objectives: making the lives of Muslim minorities easier in order to preserve their Islamic identity, and endorsing efforts to Islamize the West. To promote these objectives wasatīs emphasize a systematic search in all four religiolegal schools and beyond them and the liberal application of maslaha (public or individual interest). Some of the results achieved by this methodology demonstrate the potential of maslaha to revise any religious law relating to mu'āmalāt (social transactions). The stricter salafī approach associated with conservative elements in Saudi Arabia's religious establishment emphasizes the concept of al-walā' wa'l-barā' (loyalty and disavowal). Its juristic interpretations are based on opposition to perceived innovations, imitation of infidels and cooperation with them. I examine the two approaches through a systematic analysis of three issues that are central to the religious law of Muslim minorities: non-Muslim holidays, mortgages and service in non-Muslim militaries.